Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Economic Order Quantity (EOQ) pada Pabrik Tahu Lamongan - Adhar Putra Setiawan; Anna Marina (Universitas Muhammadiyah Ponorogo, 2026)
Lamongan Tofu Factory is a company that produces tofu, with soybeans as its main raw material. In production process activities, inventory is the most important element that must be maintained for the smooth running of the production process. The purpose of this study is to determine inventory control before and after using the Economic Order Quantity (EOQ) method.Â This research uses descriptive qualitative methods with data collection techniques, namely interviews and documentation related to the problems studied. The results of the research using the Economic Order Quantity (EOQ) method the company can purchase optimal raw materials every time they place an order of 42 tons with a frequency of ordering 25 times in one year, so that the company can save the total cost of raw material inventory of Rp 14,393,671. Lamongan Tofu Factory should consider the Economic Order Quantity (EOQ) method as in determining raw material inventory control so that the company can minimize the total inventory costs incurred.